2020
DOI: 10.1039/d0ra06977a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soybean milk fermented with Lactobacillus plantarum HFY01 isolated from yak yogurt on weight loss and lipid reduction in mice with obesity induced by a high-fat diet

Abstract: Soybean milk fermented with Lactobacillus plantarum HFY01 (LP-HFY01) was used for weight and lipid reduction in mice with obesity induced by a high-fat diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 58 publications
0
24
0
Order By: Relevance
“…Gene expression was calculated using the 2 −∆∆CT method. 15 The primer sequences are listed in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Gene expression was calculated using the 2 −∆∆CT method. 15 The primer sequences are listed in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…All mice (Kunming, male, 6-week-old) were fed a standard diet ( Table 4 ) [ 17 ] and provided with drinking water ad libitum. After adapting to the new environment for 1 week, 4 groups of mice were formed, with 10 mice in each group.…”
Section: Methodsmentioning
confidence: 99%
“…Carrageenan can induce thrombosis-related intravascular inflammation in the tail of mice, resulting in mixed thrombi filling in the venules, arterioles, and capillaries and causing ischemic necrosis of the tail tissue. The black tails of mice were observed intuitively (15). Therefore, the extent of the black tail in mice is an important experimental index to intuitively judge the degree of thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the lactic acid bacteria isolated from yak yogurt in pastoral areas are very different from the commonly-used commercial lactic acid bacteria isolated from general yogurt (11,12). Studies have demonstrated that lactic acid bacteria isolated from yak yogurt show better colonization in the intestine, as well as good preventive and interventive effects on colitis and gastritis (13,14) and good regulatory effects on hyperlipidemia (15). As such, these lactic acid bacteria have good biological activity in the body.…”
Section: Introductionmentioning
confidence: 99%